Lead Generation: Sowing the Seeds for Future Success - Konrad H. Bleicher; Matthias Nettekoven; Jens-Uwe Peters; René Wyler (CHIMIA, 2004)
Lead generation and the associated hit-to-lead process are key strategic elements in modern pharmaceutical research, and most companies have implemented this concept. Efficient lead generation is one of the main attempts to reduce the high attrition rates observed along the drug discovery process by focussing on the early developmental phases. The level of integration of the lead generation activities within the discovery organization, the flexibility in assessing and implementing new chemistries and new technologies, the high-quality standards set for the identification of the best possible chemical lead series will ultimately determine the future success in discovering new medicines.